2006
DOI: 10.1002/ceat.200500021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Effective Particle Porosity on Vacuum Fluidized Bed Drying

Abstract: A series of vacuum fluidized bed drying experiments was carried out employing particles with distinct effective porosities. The experiments showed that decreasing the operating pressure as well as increasing the operating temperature produces higher drying rates in both drying periods. In all cases, the enhancement of the drying rates was found to be more significant in the case of particles with higher effective porosities. It is concluded that lower operating pressures as well as higher operating temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…After the intersection point, the higher effective porosity of the large pepper seed particles propagates higher drying rates than those obtained with the small particles. These conclusions are supported by the results presented by Hallstrom and Wimmerstedt [31] as well as Kozanoglu et al [23] that the effective diffusivity increases with the porosity of the material. Consequently, the higher effective porosity of the large pepper seed particles also generates lower final humidity, as observed in Fig.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…After the intersection point, the higher effective porosity of the large pepper seed particles propagates higher drying rates than those obtained with the small particles. These conclusions are supported by the results presented by Hallstrom and Wimmerstedt [31] as well as Kozanoglu et al [23] that the effective diffusivity increases with the porosity of the material. Consequently, the higher effective porosity of the large pepper seed particles also generates lower final humidity, as observed in Fig.…”
supporting
confidence: 83%
“…They reported that such an arrangement of operating pressures combined the effects of a decrease in the transport capacity of the exterior medium and enhancement of the internal diffusivity, producing a favorable effect. The influence of the effective porosity over a vacuum-fluidized bed drying was experimentally studied by Kozanoglu et al [23] These researchers observed a stronger effect of operating pressure for particles with higher effective porosity. The drying behavior of porous particles in a fluidized bed operating under reduced pressure was also studied by Tatemoto et al [24,25] They experimentally observed the importance of the operating pressure and the humidity of the drying air.…”
Section: Introductionmentioning
confidence: 98%
“…Operating a fluidized bed under reduced pressures offers the possibility to eliminate these problems; lower operating temperatures, achieved under reduced pressures, decrease the degree of thermal degradation and provide a safer process outside of flammability limits. [1][2][3][4][5][6][7] A good understanding of the hydrodynamics of a reduced pressure fluidized bed is required to be able to perform a drying process properly. However, the amount of information available in the technical literature on reduced pressure fluidization is quite limited and very few papers have been published on this specific process.…”
Section: Introductionmentioning
confidence: 99%